Menstrual Characteristics of Pubertal Girls: A Questionnaire-Based Study in Turkey - Esen, Ihsan; Oguz, Baran; Serin, Hepsen Mine (Galenos Yayincilik, 2016)
Objective: Clinicians should show an awareness on the menstrual characteristics of adolescent girls which may differ from adults in some aspects. To define menstrual cycle features among high school girls residing in a city center in southeastern Turkey. Methods: A cross-sectional survey was conducted on 1256 girls attending a high school located in the city center of Elazig, Turkey. Data from 879 girls (median age, 16.2 years; range, 13.6-19.2 years) who agreed to participate in the study and had started to menstruate were evaluated. Results: Mean age at menarche was 12.7 +/- 1.3 years (range, 8.2-17.3 years). The mean cycle duration was 28.7 +/- 4.4 days, and the mean menstrual flow lasted 5.9 +/- 1.3 days. Severe, moderate, and mild dysmenorrhea was reported in 29%, 43%, and 28% of the girls, respectively, and 52% used analgesics for dysmenorrhea. A total of 34% of the girls defined their menstrual cycle as irregular, and 32% reported school absenteeism due to menstruation-associated complaints (pain and/or heavy bleeding). Menstrual bleeding affected attendance to classes and other school activities, daily work, social, family, and friend relationships, as well as sports/exercise activities in 43%, 49%, 58%, 48%, 44%, and 60% of the participants, respectively. In total, 30% of the responders had a problem with menstruation, and 12% and 17% of these stated that they consulted a primary care physician or specialist, respectively. Conclusion: Dysmenorrhea was found to be common in adolescent Turkish girls and to affect daily life in approximately half of the girls.
Keywords: Adolescent; menstrual characteristics; dysmenorrhea